Factors Influencing the Use of Electric Cigarettes in Prima Indonesia University Faculty of Medicine Students - Nasution, Masdalena; Sitorus, Aprilia Riris Margaretha; Sitohang, Widya Yanti (Newinera Publisher, 2023)
The use of e-cigarettes is becoming popular among society, especially teenagers. This study aims to determine the factors that influence the use of e-cigarettes among students at the Faculty of Medicine, Prima Indonesia University. The type of research used is an observational analytical study with a cross-sectional approach. The population in this study was 335 people. The sample in this research using non-probability sampling technique was 233 people. Data was collected through questionnaires, analyzed using the Chi-Square test, Fisher Exact test and logistic regression test. The prevalence of students who smoke is 11.48%. Variables that have a significant relationship with e-cigarette use are gender (p = <0.001; OR = 0.108 (95%CI 0.040-0.294)), friend environmental factors (p = 0.001), lifestyle environmental factors (p = 0.007; OR = 0.124 (95%CI 0.032-0.482), economic factors (p = 0.001; OR =0.133 (95%CI 0.051-0.342) and social media factors (p= 0.000; OR = 0.129 (95%CI 0.045-0.368) Meanwhile, age (p = 0.061) and family environment (p = 0.097; OR = 0.467 (95%CI 0.187-1.169) did not have a significant relationship with the use of e-cigarettes. Friends and social media were the dominant factors in the high use of cigarettes. electricity for students.